Morphological characteristics of humeri and ulnae relating to supratrochlear aperture expression - Ndou, Robert (My University, 2015)
The supratrochlear aperture (STA) is a perforation of the septum found between the olecranon and coronoid fossae of the humerus. Its prevalence is population specific and varies by sex. This study investigated the prevalence, shape and population-level variability of the STA, as well as the morphological attributes of dry humeri and ulnae according to STA expression, in South African populations (White, Mixed ethnicity and Black). The tissue found in the aperture was sampled from cadavers and studied by histochemical techniques. The objective was to identify the characteristics of STA bearing limbs in order to evaluate the possible etiology and function of the aperture. The overall prevalence of the STA among South Africans was found to be 32.5%. Significant population differences exist, with Whites having the lowest rate of 16% and Sotho peoples expressing the highest prevalence of 41% among the Black group. The STA was more prevalent in females and on the left arm. In bilateral cases, females had twice the prevalence rate. Osteometric measures of bone size were used to test the propositions that robust humeri are less prone to STA formation and that pressure from the ulnar olecranon and coronoid processes may result in an STA. Most measures of overall humeral size, such as epicondylar breadth, humeral head circumference and the three shaft circumferences, were significantly larger when the STA was absent in all three populations. This supports the general proposition that gracile bones are prone to septal perforation. However, an important result of this study is the finding from the discriminant analyses that determinants of STA status are population specific. For Blacks and the Mixed group, the olecranon process length was the sole main contributor to STA status. Lower loadings for this variable were found for the Mixed group. Therefore, this variable can more reliably predict STA status in Blacks compared to the Mixed group. In Whites, with a lower prevalence of the STA, more parameters are required for STA prediction compared to the Mixed group or Blacks. These additional parameters were proximal humeral shaft circumference (right) and trochlear notch depth (left). The presence of dense connective tissue found crossing the aperture needs to be explained as it appears to be a feature unique to the distal humerus. It is possible that the STA forms as a result of incomplete remodeling in response to pressure from the olecranon process. The result would be bone resorption and subsequent osteoblastic secretion of collagen, but no incorporation of hydroxyapatite occurs – rendering the aperture region pliant and able to withstand the continuing force of the olecranon during joint motion. As to the function of the STA covering tissue, it may be of considerable structural strength in light of its dense regular connective tissue composition. It is strongly attached to the bony septum in a manner comparable to the way tendons attach to bone, suggesting a need for structural strength. One explanation for this particular feature of the tissue may be that it functions to prevent locking the olecranon process in the joint. An additional aspect to be considered regarding function of the STA is that the mean extension angle in the STA bearing arms was greater. This implies that the olecranon process tip may penetrate the aperture (as observed on many dry humeri, when articulated with ulnae and elbow joints maximally extended), permitting a greater extension angle. It follows that the elbow range of motion is greater in STA individuals. Based on orthopedic surgical experience, bones with the STA are thought to have a narrower medullary canal. Humeri with the STA in our study did appear to have narrower medullary canal dimensions. However, this was not the case after standardizing for bone size. The smaller medullary canal width observed in STA humeri is due to the bone size differences rather than the presence of the STA. We therefore propose that bone size be the major factor to consider when making choices of a rod for intramedullary fixation.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in accomplishment of the requirements for the degree of DOCTOR OF PHILOSOPHY 25 May 2015